The relationship between share repurchase frequency and firms financial characteristics: A study in Malaysia - Izzatulamal, Sabarani (2014)
The purpose of this study is to examine the relationship between different frequency of share repurchase program and firm financial characteristic in Malaysia. The number of Malaysia firms buying back their own shares on the open market has been increasing since 1997 subsequent to the Asian Financial crisis. This study fills the gap by examining the relevant determinants of the firm financial characteristics that may lead to the different frequency of share buyback of a company. Infrequency share buyback firms engage in between (1-3 programs) while frequent buyback firms are categorized as having engaged in between (4-5 programs). The findings of this study showed that market to book value and earnings per share are the variables that affect share repurchase frequently significantly. This study contributed to the understanding of the scant literature of frequency on share buyback in Malaysia. This study also contributes to the explanation of the signalling hypothesis regarding the buyback frequency program explained by the findings.